The contribution of coaching and mentoring to development of the participants in the Small Business Academy programme of the University of Stellenbosch Business School - Cronje, Jean Pierre (Stellenbosch : Stellenbosch University, 2016)
Thesis (MA)--Stellenbosch University, 2015.